2019
DOI: 10.1371/journal.pone.0221344
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas sobria serine protease decreases epithelial barrier function in T84 cells and accelerates bacterial translocation across the T84 monolayer in vitro

Abstract: Aeromonas sobria is a pathogen causing food-borne illness. In immunocompromised patients and the elderly, A . sobria can leave the intestinal tract, and this opportunistically leads to severe extraintestinal diseases including sepsis, peritonitis, and meningitis. To cause such extraintestinal diseases, A . sobria must pass through the intestinal epithelial barrier. The mechanism of such bacterial translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…recognize the exogenous PAMPs or its released DAMPs. Previous studies on A. sobria were mainly focused on the case reports in humans, and several studies were about the characteristics and functions of virulence factor serine protease in colonic epithelial cells (Kobayashi, 2011;Kobayashi et al, 2019;Song et al, 2019). However, the interactions between A. sobria and host cells' innate immunity have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…recognize the exogenous PAMPs or its released DAMPs. Previous studies on A. sobria were mainly focused on the case reports in humans, and several studies were about the characteristics and functions of virulence factor serine protease in colonic epithelial cells (Kobayashi, 2011;Kobayashi et al, 2019;Song et al, 2019). However, the interactions between A. sobria and host cells' innate immunity have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Serine proteases (SP) are associated with liquefaction of muscle tissue resulting in lesion formation (Whitby, Landon, & Coleman, 1992). It has also been suggested that SP could be involved in the development of extraintestinal diseases such as sepsis, peritonitis and meningitis because of their ability to decrease epithelial barrier function and accelerate bacterial translocation (Kobayashi et al., 2019). After penetration, SP could contribute to septic shock through interaction with plasma proteins and increase haemorrhagic tendencies in sepsis (Imamura, Nitta, Wada, Kobayashi, & Okamoto, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We added bacterial cells (MOI = 5) suspended in HBSS containing 15 mM HEPES (pH 7.4) to the apical side of T84 cells cultured in 12-well microplates. In our earlier study, the degradation of the protein components constituting the junctional complexes was observed to start early (Kobayashi et al, 2019). As in that study, we analyzed the degradation of the protein components constituting TJs at 2 hr post-infection.…”
Section: Analyses Of the Degradation Of The Protein Components Consti...mentioning
confidence: 93%
“…To test this hypothesis, we performed an in vitro analysis using cultured T84 cells ( Kobayashi et al., 2019 ), and we observed that ASP acts on AJs and causes the destruction of both nectin-2 and afadin (protein components constituting AJs). We suspect that the destruction of nectin-2 and afadin by the action of ASP ( i ) increases the ability of A. sobria to pass through intestinal epithelial tissue, and ( ii ) contributes to the severity of pathological conditions.…”
Section: Introductionmentioning
confidence: 99%